Assessing the Effects of New Legislation on Tax Planning Strategies - Yogaswara, Wira (Advances in Taxation Research, 2023)
Purpose: This study examines the impact of new tax legislation on tax planning strategies, considering various socio-economic, psychological, and institutional factors. Research Design and Methodology: This study leverages a synthesis of existing literature and theoretical frameworks to analyze the complex dynamics that shape taxpayer behavior and regulatory response. Findings and Discussion: The findings suggest that changes in tax laws drive strategic adjustments in taxpayer behavior, reflecting efforts to optimize financial outcomes within a regulatory framework. They emphasize the importance for policymakers to consider taxpayer responses when designing tax reforms to minimize unintended consequences and gaps in tax planning practices. Moreover, differences across demographic, socio-economic, and organizational parameters highlight the need for equitable tax policy design.   Implications: The implications of this study include practical interventions and policy decisions. It emphasizes the importance of increasing taxpayer education, simplifying tax laws, and improving access to support services to encourage voluntary compliance and reduce tax evasion.